2020
DOI: 10.1002/mc.23266
|View full text |Cite
|
Sign up to set email alerts
|

RNA‐seq reveals novel cancer‐selective and disease subtype‐independent mechanistic targets of withaferin A in human breast cancer cells

Abstract: Withaferin A (WA) exhibits cancer chemopreventive efficacy in preclinical models representative of two different subtypes of breast cancer. However, the mechanism(s) underlying breast cancer chemoprevention by WA is not fully elucidated. We performed RNA‐seq analyses using a non‐tumorigenic mammary epithelial cell line (MCF‐10A) and human breast cancer cells (BCC) belonging to the luminal‐type (MCF‐7), HER2‐enriched (SK‐BR‐3), and basal‐like subtype (MDA‐MB‐231) to identify novel cancer‐selective mechanistic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…Thus, the enhanced Nrf2 bound with AREs in order to upregulate its downstream antioxidant enzymes. Robust induction of Nrf2 by WFA was recently reported in the treatment of human breast cancer cells [129]. This study concluded that Nrf2 helped in the mediation of apoptosis and autophagy in several breast cancer cells.…”
Section: Withaferin a (Wfa)supporting
confidence: 65%
“…Thus, the enhanced Nrf2 bound with AREs in order to upregulate its downstream antioxidant enzymes. Robust induction of Nrf2 by WFA was recently reported in the treatment of human breast cancer cells [129]. This study concluded that Nrf2 helped in the mediation of apoptosis and autophagy in several breast cancer cells.…”
Section: Withaferin a (Wfa)supporting
confidence: 65%
“…Although HSPA6 was discovered three decades ago, the functional roles in cancer progression are unclear ( 12 14 ). Recently, HSPA6 was discovered to be dispensable for Withaferin A-mediated apoptosis/autophagy or migration inhibition of breast cancer ( 15 ). In this study, RNA-sequencing (RNA-seq) was performed and TQ-targeted gene HSPA6 was successfully identified for TNBC inhibition functionally.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptotic cell death was quantitated by flow cytometry following staining with Annexin V and PI essentially as described by us previously [ 28 ]. Briefly, the MEFs were plated in 6-well plates at a density of 2 × 105 cells/well and incubated overnight to allow attachment.…”
Section: Methodsmentioning
confidence: 99%